Pelatihan dan Pembuatan Handsanitizer serta Handsanitizer Stand Untuk RT 07 RW 21 Modinan, Gamping, Sleman, Yogyakarta - Saputra, Hadi; Hastutiningrum, Sri; Pratiwi, Yuli (DHARMA BAKTI, 2022)
Coronavirus disease (COVID-19) is an infectious disease caused by the discovery of a new coronavirus. This disease occurs as a result of COVID-19 infection in the respiratory tract. Transmission of this disease occurs due to droplets when sneezing. Prevention and slowdown of transmission can be done by implementing health protocols. Respiratory etiquette includes using a mask, washing hands with a hand sanitizer, and using a safe hand-sanitizer stand. The propose of this social wellfare is to condact training on the manufacture of hansanitizer and foot hand sanitizer stands that are safe, inexpensive, and easy to manufacture and are needed by residents who are economically affected during the pandemic. The result of this service to the community has resulted in a hand-sanitizer stand prototype design that is easy and inexpensive to be made independently by the district.